Pengaruh Tangible dan Reliability Jasa Hotel terhadap Tingkat Kepuasan Konsumen di Rumah Kito Resort Hotel Jambi - Ahmad Tarmizi; Akhmad Irwansyah; Bella Ahiri Ramadani (Ekonomis: Journal of Economics and Business, 2022)
This study aims to determine the effect of tangible and reliability on consumer satisfaction simultaneously and the effect of tangible and reliability on customer satisfaction partially. The type of data used in this research is quantitative primary data regarding tabulation of data from questionnaires. The data in this study can be obtained from a questionnaire at Rumah Kito Resort Hotel Jambi. The sample of this research is Rumah Kito Resort Hotel Jambi, with a population of 13,250 people and a sample of 100 people. This study uses an analytical tool, namely multiple linear regression. The results of this study indicate that: tangibles are categorized as good with an average score of 396, reliability is categorized as good with an average score of 405, and consumer satisfaction is categorized as good with an average score of 413. Based on the results of the study, it can be concluded Based on the results of the coefficient of determination test, it can be seen that Tangible and Reliability have an influence on Consumer Satisfaction at Rumah Kito Resort Hotel by 0.506 or 50.6% stating that tangible and reliability variables are able to explain Customer Satisfaction of 50.6 % on the contrary 49.4% caused by other variables outside the variables studied, Based on the results of the t-test, it can be said that the t-value on the Tangible variable is 2.696 with a significant level of 0.000. Because the t-count value is 2,696 > the t-table value is 1.660 and the significant level is 0.000 < significant probability = 0.05. While the value of t-count on the reliability variable is 5.540 with a significant level of 0.000. Because the t-count value is 5.540 > t-table 1.660 and the significant level is 0.000 < significant probability = 0.05.